Should Wine History Have a Post-colonial Future? British Imperial Viticulture and Settler Colonialism - Regan-Lefebvre, Jennifer (Journal of the Canadian Historical Association / Revue de la Société historique du Canada)

(untitled) (The Canadian Historical Association / La Société historique du Canada, 2023)
As the history of wine emerges as a field of scholarly study, scholars may wish to consider the historiographical and theoretical approaches best suited to its study, particularly in regards to recent research into the central role of colonization in the global spread of viticulture. This article gives an overview of some major historiographical approaches to wine history, noting the general absence of overarching discussions of imperialism and colonialism. Then, to illustrate some of the complexities of applying these frameworks, it considers two related stories, and briefly retells them through each of three theoretical lenses. The first story is of the creation and operation of the Burgoyne Company, the major British importer of Australian and South African wine from the 1870s through the 1950s. The second story is of Burgoyne, and others, importing their wine into the Irish market. These microhistories illustrate what is potentially at stake, and what is complicated, in incorporating colonial and post-colonial frameworks into our understanding of wine history.